2015
DOI: 10.5551/jat.27391
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness Predicts Cognitive Decline in Japanese Community-dwelling Elderly Subjects: A One-year Follow-up Study

Abstract: Aim:The purpose of this study was to determine whether arterial stiffness can be used to predict one-year changes in the cognitive function in Japanese community-dwelling elderly subjects. Methods: A total of 103 Japanese community-dwelling elderly patients joined this study. Information regarding the age, height, weight, gender and past medical history of each participant was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
2
8
2
Order By: Relevance
“…Microvascular brain damage, such as microinfarction, microhemorrhage, and macrohemorrhage 3, 4) , as well as peripheral arterial stiffness 5, 6) , heighten the risk of cognitive impairment. Previous studies have suggested that such brain abnormalities may be associated with retinal vascular changes due to shared embryological, anatomical, and physiological features 79) .…”
Section: Introductionmentioning
confidence: 99%
“…Microvascular brain damage, such as microinfarction, microhemorrhage, and macrohemorrhage 3, 4) , as well as peripheral arterial stiffness 5, 6) , heighten the risk of cognitive impairment. Previous studies have suggested that such brain abnormalities may be associated with retinal vascular changes due to shared embryological, anatomical, and physiological features 79) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies have also shown novel associations between cognitive impairment and arterial stiffness [10][11][12][13][14][15] . Methods for assessing arterial stiffness are noninvasive and allow simple assessment and data evaluation.…”
Section: Outlinementioning
confidence: 99%
“…Thus, an increased ABI indicates arterial calcification that leads to vessel sclerosis (advanced vessel stiffness). Increased PWV is also associated with cognitive impairment [12,14] , an independent predictor of cognitive decline [10,11] , and β-amyloid (Aβ) deposition in the brains of older patients [15] . More specifically, Hughes et al [15] showed the associations between arterial stiffness and Aβ deposition in the brain independent of blood pressure.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…WMH are a well‐known risk factor for cognitive impairment . Cognitive impairment including dementia is also independently associated with arterial stiffness . An ABI greater than 1.30 and increased blood pressure variability are important predictors of cognitive impairment among patients without vascular diseases .…”
Section: Wmh and Arterial Stiffnessmentioning
confidence: 99%
“…20 Cognitive impairment including dementia is also independently associated with arterial stiffness. [21][22][23][24] An ABI greater than 1.30 and increased blood pressure variability are important predictors of cognitive impairment among patients without vascular diseases. 21 Furthermore, increased PWV is associated with cognitive impairment, 25 an independent predictor of cognitive decline, 23 and β-amyloid deposition in the brains of older adults.…”
Section: Cognitive Impairmentmentioning
confidence: 99%